Effect of Replacing Dietary Fish Meal with Silkworm (Anaphe infracta) Caterpillar Meal on Growth, Digestibility and Economics of Production of Starter Broiler Chickens - Ijaiya, A.T.; Eko, E.O. (Pakistan Journal of Nutrition, 2009)
A total of one hundred and fifty day-old anak broiler chicks were used to investigate the replacement value of silkworm caterpillar meal (SCM) for fish meal (FM) on growth performance, nutrient digestibility and cost benefit of starter broilers. The birds were randomly allotted to five treatment groups of 30 birds with each treatment having two replicates of 15 birds each. Five isocaloric and isonitrogenous diets were formulated such that diet 1 which served as the control had 100% FM:0% SCM while diets 2, 3, 4 and 5, respectively) had: 75% FM:25% SCM;50% FM:50% SCM;25% FM:75% SCM and 0%FM: 00% SCM, respectively. The birds were given feed and water ad-libitum. The performance in terms of feed intake (29.51-31.66g), body weight gain (16.56-19.03g), feed conversion efficiency (FCR) (1.60-1.72), protein efficiency ratio (PER) (2.67-2.77) and nutrient digestibility of the chicks indicated no significant (P > 0.05) differences among the treatment means. Cost per kg gain gradually declined with increasing dietary level of SCM indicating higher economic benefit. The results of this study demonstrated that cheaper silkworm caterpillar meal can be an excellent substitute for fish meal in formulating diets for starter broiler chicks leading to increased economic gains.